Antifouling coating and its preparation method and application
By combining modified nano-concave and convex rod soil and fluorinated paraffin, the problem of insufficient wear resistance of existing coatings in high wear environments is solved, better dispersion and anti-fouling effect are achieved, and the overall performance of the coating is improved. .
Patent Information
- Application Number
- CN202411797433.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing fluorosilic modified acrylic resin antifouling coatings are insufficient in high wear environments, and the dispersion and binding force of nano-silica are insufficient, which affects the overall performance of the coating.
Modifying nano-concave stick soil, using 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexanyl)ethyltriethoxysilane to enhance nano-concave stick soil The surface activity and dispersion of the coating are combined with fluorinated paraffin and cerium citrate to form a denser crosslinking network, improving the mechanical strength and wear resistance of the coating.
It significantly improves the wear resistance and dispersion of the coating, enhances the overall anti-fouling effect of the coating, and improves the adhesion and durability of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an antifouling coating and a preparation method and application thereof. Background Art
[0002] Ships, nets and cages are immersed in seawater for a long time and are easily damaged by seawater, wave impact and the attachment of marine organisms. Therefore, antifouling coatings are needed on their surfaces to avoid the attachment of microorganisms and erosion by seawater.
[0003] As a high-performance coating material, fluorosilicone modified acrylic resin has excellent weather resistance, chemical resistance and low surface energy, and has broad application prospects in the field of antifouling coatings. However, its wear resistance still needs to be further improved, and it is difficult to meet the requirements of high-wear environments such as ships and cages. The invention patent with publication number CN112574629A discloses a water-based antifouling coating containing fluorosilicone modified acrylic resin. The coating contains wear-resistant nano-silicon dioxide. Since nano-silicon dioxide is easy to agglomerate, the dispersion is poor, and the binding force with the resin is insufficient, the overall performance of the coating is affected. Summary of the invention
[0004] In view of this, the present invention proposes an antifouling coating with high wear resistance and good dispersibility, and a preparation method and application thereof.
[0005] The technical solution of the present invention is implemented as follows: In the first aspect, the present invention provides an antifouling coating, the antifouling coating comprising component A and component B, wherein component A comprises: fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano attapulgite, a wetting agent, a defoaming agent and a dispersant;
[0006] The modified nano-attapulgite modifier is prepared from 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0007] Component B includes: curing agent and diluent.
[0008] Specifically, nano-attapulgite is a natural porous material that has better surface activity and dispersibility after modification. The modified nano-attapulgite can provide enhanced mechanical properties, such as improved wear resistance. The porous structure and chemical modification make attapulgite effective in improving the mechanical strength and wear resistance of coatings.
[0009] 2-Imidazole-1-ylethylamine is a compound containing an imidazole ring. This group has good reactivity and can undergo a ring-opening reaction with the epoxy group of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane to form a chemical bond. The modifier generated by this step of reaction contains imidazole and silane double groups. The silane functional group of the modifier can form a Si-O-Si bond through the hydrolysis condensation reaction of the silane group, and a more stable silicon-oxygen network structure can be attached to the surface of the nano-attapulgite.
[0010] After chemical modification, the surface chemical properties of nano-attapulgite are changed. The imidazole group increases its compatibility with organic substrates (such as 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, fluorinated paraffin, etc.), which greatly improves its dispersibility in the coating matrix. The silane groups modified on the surface of nano-attapulgite can undergo cross-linking reactions with other network structures during the curing process of the coating to form a denser cross-linked network, thereby improving the mechanical strength and wear resistance of the coating. The nano-size effect of attapulgite and the better dispersibility after modification make the coating less susceptible to wear when subjected to mechanical force. The uniform distribution of modified attapulgite in the coating forms a physical barrier, preventing external friction from directly acting on the coating matrix and protecting the coating from damage.
[0011] Fluorinated paraffin is a fluorine compound whose fluorine atoms can form a tight protective barrier to reduce the contact between pollutants and the substrate. The porosity and large specific surface area of modified attapulgite can help better disperse fluorinated paraffin and enhance its uniformity and effectiveness in the coating. In addition, attapulgite can enhance the coating's resistance to mechanical damage, while fluorinated paraffin further reduces the physical adhesion of pollutants. The combination of the two can significantly enhance the overall antifouling effect of the coating.
[0012] On the basis of the above technical scheme, preferably, calculated by weight, the component A includes: 50-70 parts of fluorosilicone modified acrylic resin, 5-8 parts of fluorinated paraffin, 10-15 parts of modified nano-attapulgite, 1-3 parts of wetting agent, 1-3 parts of defoaming agent, and 3-5 parts of dispersant; the component B includes, calculated by weight, 4-6 parts of curing agent and 1-3 parts of diluent; the weight ratio of component A:component B is 8-10:1.
[0013] On the basis of the above technical solution, preferably, the component A further comprises 1-2 parts by weight of cerium citrate.
[0014] Cerium citrate can improve the adhesion of coatings, which is crucial to the overall performance of coatings. The cerium ions in cerium citrate can interact with certain functional groups in the resin through chelation to improve the adhesion and toughness of the coating, which helps prevent the coating from separating from the substrate and enhances the wear resistance and durability of the coating. Cerium compounds also have good antioxidant properties, which can protect the resin matrix from damage by ultraviolet rays and oxidative environments, delay the degradation process of the resin, and thus improve the overall weather resistance and service life.
[0015] In addition, cerium citrate can lock the position of fluorinated paraffin in the coating by increasing viscosity or cross-linking. This stabilizing effect helps to enhance and last the hydrophobicity and antifouling properties of the coating. When combined with fluorinated paraffin, cerium citrate can provide enhanced thermal stability and slow down the degradation of fluorinated paraffin under high temperature or long-term exposure conditions. Cerium citrate can also improve the dispersibility of modified attapulgite in the coating matrix, mainly through its chelation effect to reduce the agglomeration between particles, ensure its more uniform distribution in the coating, and improve the comprehensive mechanical properties of the material.
[0016] In summary, the combination of cerium citrate and attapulgite improves the overall performance of the composite material, especially in terms of wear resistance and anti-stripping. The presence of cerium compounds also reduces the degradation rate of modified attapulgite in harsh environments.
[0017] On the basis of the above technical scheme, preferably, the preparation method of the nano-modified attapulgite is: in a nitrogen atmosphere, 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are reacted at 140-160°C and catalyzed by boron trifluoride ether for 4-5 hours to obtain a modifier; the nano-attapulgite is treated with arc plasma at a DC voltage of 30-50kW for 5-10 minutes to obtain activated nano-attapulgite, followed by ultrasonication in an isopropanol aqueous solution for 20-30 minutes to obtain a suspension, and then the modifier is added, and the ultrasonication is continued for 20-30 minutes, followed by reflux reaction under a nitrogen atmosphere for 3-4 hours, and filtration to obtain modified nano-attapulgite.
[0018] The activated nano-attapulgite after arc plasma pretreatment has more reaction sites, which improves the interfacial bonding strength. This bonding not only improves the dispersibility and stability of attapulgite in the resin matrix, but also enhances the overall flexibility and mechanical properties of the coating.
[0019] On the basis of the above technical scheme, preferably, the molar ratio of the 2-imidazole-1-ylethylamine:2-(3,4-epoxycyclohexyl)ethyltriethoxysilane is 1:1-3, and the amount of the boron trifluoride ether is 1%-3% of the total weight of the 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
[0020] On the basis of the above technical solution, preferably, the mass ratio of the nano-attapulgite:modifier is 1:1-2.
[0021] On the basis of the above technical scheme, preferably, the wetting agent is fatty alcohol polyoxyethylene ether; the defoaming agent is a polyether defoaming agent; the dispersing agent is a mixture of one or more of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-hydroxyethyl-3-methylimidazolium acetate, 1-hydroxypropyl-3-methylimidazolium acetate and 1-hydroxypropyl-3-methylimidazolium tetrafluoroborate; the curing agent is an isocyanate curing agent, and the diluent is one of trimethylolpropane glycidyl ether, ethylene glycol glycidyl ether and tert-butyl glycidyl ether.
[0022] In a second aspect, the present invention provides a method for preparing an antifouling coating, comprising the following steps:
[0023] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, a wetting agent, a defoaming agent and a dispersant, and stirring to obtain component A;
[0024] S2, mixing the curing agent and the diluent in the formula amount, stirring, to obtain component B;
[0025] S3, mix the A component and the B component in the formula amount, stir, and obtain.
[0026] On the basis of the above technical solution, preferably, in steps S1-S3, the stirring speed is 800-1500 rpm and the time is 10-30 min.
[0027] In a third aspect, the present invention provides an application of an antifouling coating in ships and nets and cages.
[0028] The antifouling coating of the present invention and its preparation method and application have the following beneficial effects compared with the prior art:
[0029] (1) The present invention modifies nano-attapulgite by using 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, which improves the dispersibility of nano-attapulgite in the coating on the one hand, and improves the compatibility with the resin on the other hand, so that it can undergo cross-linking reactions with other network structures during the curing process of the coating to form a denser cross-linked network, thereby improving the mechanical strength and wear resistance of the coating. In addition, the modified attapulgite can also better disperse paraffin fluoride and enhance its uniformity and effectiveness in the coating. The modified attapulgite can enhance the coating's resistance to mechanical damage, while the paraffin fluoride further reduces the physical adhesion of pollutants. The combination of the two can significantly enhance the overall anti-fouling effect of the coating.
[0030] (2) The present invention adds cerium citrate to the antifouling coating to enhance the adhesion of the coating, prevent the coating from separating from the substrate, and enhance the wear resistance and durability of the coating. Cerium citrate can also lock the position of fluorinated paraffin in the coating, which helps the coating maintain long-lasting hydrophobicity and antifouling properties; at the same time, it can also slow down the degradation of fluorinated paraffin that may occur under high temperature or long-term exposure conditions. Cerium citrate can also improve the dispersibility of modified attapulgite in the coating matrix, ensure its more uniform distribution in the coating, and improve the comprehensive mechanical properties of the material. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Fluorosilicone modified acrylic resin (LuCure ® 5158) was purchased from Guangzhou Runao Chemical Materials Co., Ltd.; 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, CAS: 10217-34-2, was purchased from Shandong Yinglang Chemical Co., Ltd.; rare earth citric acid salts were purchased from Hangzhou Dingyan Chemical Co., Ltd.; polyether defoamers (models P-20, P-12, P-06) were all purchased from Shandong Meiyu Chemical Co., Ltd.; fatty alcohol polyoxyethylene ether penetrant was purchased from Jinan Yutao Chemical Co., Ltd., model O-25.
[0033] Example 1
[0034] The antifouling coating of this embodiment includes component A and component B, component A includes: 58g of fluorosilicone modified acrylic resin, 6g of fluorinated paraffin, 13g of modified nano-attapulgite, 2.5g of fatty alcohol polyoxyethylene ether, 1.5g of polyether defoamer P-20, and 4g of 1-hydroxyethyl-3-methylimidazole tetrafluoroborate; component B includes: 5g of isocyanate curing agent and 2g of trimethylolpropane glycidyl ether; the weight ratio of component A: component B is 9:1.
[0035] The preparation method of modified nano-attapulgite comprises the following steps:
[0036] S1, under nitrogen atmosphere, 1 mol 2-imidazole-1-ylethylamine and 2 mol 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane were reacted at 140°C for 5 h under the catalysis of boron trifluoride ether to prepare the modifier; the amount of boron trifluoride ether was 1.5% of the total weight of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0037] S2, treating the nano-attapulgite with arc plasma at a DC voltage of 40 kW for 8 minutes to obtain activated nano-attapulgite, then taking 20 g of the activated nano-attapulgite and ultrasonicating it in 120 g of isopropanol aqueous solution (volume fraction 75%) for 25 minutes to obtain a suspension, and then adding 20 g of the modifier prepared in step S1, continuing ultrasonicating it for 20 minutes, and then reflux reacting it under a nitrogen atmosphere for 3.5 hours, filtering it, and obtaining the modified nano-attapulgite.
[0038] The preparation method of the antifouling coating comprises the following steps:
[0039] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, fatty alcohol polyoxyethylene ether, polyether defoamer P-20 and 1-hydroxyethyl-3-methylimidazole tetrafluoroborate, and stirring at 800 rpm for 10 min to obtain component A;
[0040] S2, mixing the isocyanate curing agent and trimethylolpropane glycidyl ether in the formula amount, stirring at 1200 rpm for 20 min, to obtain component B;
[0041] S3, mix the A component and the B component in the formula amount, and stir at 1500 rpm for 30 minutes to obtain.
[0042] Example 2
[0043] The difference between Example 2 and Example 1 is that 1.5 g of cerium citrate is added to component A, and the rest of the contents are the same as Example 1.
[0044] Example 3
[0045] The antifouling coating of this embodiment includes component A and component B, component A includes: 50g of fluorosilicone modified acrylic resin, 5.5g of fluorinated paraffin, 11g of modified nano-attapulgite, 1g of cerium citrate, 1g of fatty alcohol polyoxyethylene ether, 1g of polyether defoamer P-122g, and 5g of 1-hydroxyethyl-3-methylimidazole acetate; component B includes: 4g of isocyanate curing agent and 1g of ethylene glycol glycidyl ether; the weight ratio of component A:component B is 10:1.
[0046] The preparation method of modified nano-attapulgite comprises the following steps:
[0047] S1, under nitrogen atmosphere, 1 mol 2-imidazole-1-ylethylamine and 1 mol 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane were reacted at 150°C for 4 h under the catalysis of boron trifluoride ether to prepare the modifier; the amount of boron trifluoride ether was 1% of the total weight of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0048] S2, treating the nano-attapulgite with arc plasma at a DC voltage of 30 kW for 10 minutes to obtain activated nano-attapulgite, then taking 20 g of the activated nano-attapulgite and ultrasonicating it in 100 g of isopropanol aqueous solution (volume fraction 75%) for 30 minutes to obtain a suspension, then adding 30 g of a modifier, continuing ultrasonicating it for 25 minutes, and then reflux reacting it under a nitrogen atmosphere for 3 hours, filtering it, and obtaining the modified nano-attapulgite.
[0049] The preparation method of the antifouling coating comprises the following steps:
[0050] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, fatty alcohol polyoxyethylene ether, polyether defoamer P-12 and 1-hydroxyethyl-3-methylimidazole acetate, and stirring at 1000 rpm for 20 min to obtain component A;
[0051] S2, mixing the cyanate curing agent and ethylene glycol glycidyl ether in the formula amount, stirring at 1200 rpm for 10 min, to obtain component B;
[0052] S3, mix the A component and the B component in the formula amount, and stir at 1500 rpm for 10 min to obtain.
[0053] Example 4
[0054] The antifouling coating of this embodiment includes component A and component B, component A includes: 70g of fluorosilicone modified acrylic resin, 5g of fluorinated paraffin, 15g of modified nano-attapulgite, 1.7g of cerium citrate, 1.5g of fatty alcohol polyoxyethylene ether, 3g of polyether defoamer P-06, and 4.5g of 1-hydroxypropyl-3-methylimidazole acetate; component B includes: 6g of isocyanate curing agent and 3g of tert-butyl glycidyl ether; the weight ratio of component A:component B is 8:1.
[0055] The preparation method of modified nano-attapulgite comprises the following steps:
[0056] S1, under nitrogen atmosphere, 1 mol 2-imidazole-1-ylethylamine and 3 mol 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane were reacted at 160°C for 5 h under the catalysis of boron trifluoride ether to prepare the modifier; the amount of boron trifluoride ether was 3% of the total weight of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0057] S2, treating the nano-attapulgite with arc plasma at a DC voltage of 50 kW for 5 minutes to obtain activated nano-attapulgite, then taking 20 g of the activated nano-attapulgite and ultrasonicating it in 160 g of isopropanol aqueous solution (volume fraction 75%) for 25 minutes to obtain a suspension, then adding 40 g of a modifier, continuing ultrasonicating it for 25 minutes, and then reflux reacting it under a nitrogen atmosphere for 3.5 hours, filtering it, and obtaining the modified nano-attapulgite.
[0058] The preparation method of the antifouling coating comprises the following steps:
[0059] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, fatty alcohol polyoxyethylene ether, polyether defoamer P-06 and 1-hydroxypropyl-3-methylimidazole acetate, and stirring at 850 rpm for 10 min to obtain component A;
[0060] S2, mixing the isocyanate curing agent and tert-butyl glycidyl ether in the formula amount, stirring at 1050 rpm for 20 min, to obtain component B;
[0061] S3, mix the A component and the B component in the formula amount, and stir at 1250 rpm for 10 min to obtain.
[0062] Example 5
[0063] The antifouling coating of this embodiment includes component A and component B, component A includes: 65g of fluorosilicone modified acrylic resin, 8g of fluorinated paraffin, 10g of modified nano-attapulgite, 2g of cerium citrate, 3g of fatty alcohol polyoxyethylene ether, 1g of polyether defoamer P-06, and 3g of 1-hydroxypropyl-3-methylimidazole tetrafluoroborate; component B includes: 5.5g of isocyanate curing agent and 2.5g of trimethylolpropane glycidyl ether; the weight ratio of component A: component B is 9:1.
[0064] The preparation method of modified nano-attapulgite comprises the following steps:
[0065] S1, under nitrogen atmosphere, 1 mol 2-imidazole-1-ylethylamine and 2 mol 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane were reacted at 155°C for 4.5 h under the catalysis of boron trifluoride ether to prepare the modifier; the amount of boron trifluoride ether was 2.5% of the total weight of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0066] S2, the nano-attapulgite is treated with arc plasma at a DC voltage of 35 kW for 8 minutes to obtain activated nano-attapulgite, and then 20 g of the activated nano-attapulgite is ultrasonicated in 130 g of isopropanol aqueous solution (volume fraction 75%) for 30 minutes to obtain a suspension, and then 25 g of a modifier is added, and the ultrasonication is continued for 20 minutes, followed by reflux reaction under a nitrogen atmosphere for 3.5 hours, and filtered to obtain the modified nano-attapulgite.
[0067] The preparation method of the antifouling coating comprises the following steps:
[0068] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, fatty alcohol polyoxyethylene ether, polyether defoamer P-06 and 1-hydroxypropyl-3-methylimidazole tetrafluoroborate, and stirring at 800 rpm for 10 min to obtain component A;
[0069] S2, mixing the isocyanate curing agent and trimethylolpropane glycidyl ether in the formula amount, stirring at 1200 rpm for 30 min, to obtain component B;
[0070] S3, mix the A component and the B component in the formula amount, and stir at 1500 rpm for 20 minutes to obtain.
[0071] Example 6
[0072] The antifouling coating of this embodiment includes component A and component B, component A includes: 65g of fluorosilicone modified acrylic resin, 7g of fluorinated paraffin, 14g of modified nano-attapulgite, 1.9g of cerium citrate, 2.3g of fatty alcohol polyoxyethylene ether, 2.5g of polyether defoamer P-20, and 3.5g of 1-hydroxyethyl-3-methylimidazole tetrafluoroborate; component B includes: 4.5g of isocyanate curing agent and 1.5g of trimethylolpropane glycidyl ether; the weight ratio of component A:component B is 9.5:1.
[0073] The preparation method of modified nano-attapulgite comprises the following steps:
[0074] S1, under nitrogen atmosphere, 1 mol 2-imidazole-1-ylethylamine and 2 mol 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane were reacted at 145°C for 5 h under the catalysis of boron trifluoride ether to prepare the modifier; the amount of boron trifluoride ether was 1.5% of the total weight of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane;
[0075] S2, treating the nano-attapulgite with arc plasma at a DC voltage of 45 kW for 10 minutes to obtain activated nano-attapulgite, then taking 20 g of the activated nano-attapulgite and ultrasonicating it in 150 g of isopropanol aqueous solution (volume fraction 75%) for 30 minutes to obtain a suspension, then adding 30 g of a modifier, continuing ultrasonicating it for 30 minutes, then refluxing it under a nitrogen atmosphere for 4 hours, filtering it, and obtaining the modified nano-attapulgite.
[0076] The preparation method of the antifouling coating comprises the following steps:
[0077] S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, fatty alcohol polyoxyethylene ether, polyether defoamer P-06 and 1-hydroxypropyl-3-methylimidazole tetrafluoroborate, and stirring at 1000 rpm for 10 min to obtain component A;
[0078] S2, mixing the isocyanate curing agent and trimethylolpropane glycidyl ether in the formula amount, stirring at 1200 rpm for 10 min, to obtain component B;
[0079] S3, mix the A component and the B component in the formula amount, and stir at 1500 rpm for 30 minutes to obtain.
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that the nano-attapulgite is not modified but directly added, and the rest of the contents are the same as Example 1.
[0082] Comparative Example 2
[0083] The difference between Comparative Example 2 and Example 1 is that the modifier is only 2-imidazole-1-ylethylamine, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane is missing. The rest of the contents are the same as Example 1.
[0084] Comparative Example 3
[0085] The difference between Comparative Example 3 and Example 1 is that the modifier is only 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and 2-imidazole-1-ylethylamine is missing. The rest of the contents are the same as Example 1.
[0086] Comparative Example 4
[0087] The difference between Comparative Example 4 and Example 1 is that the nano-attapulgite is not activated, and the rest of the contents are the same as Example 1.
[0088] Comparative Example 5
[0089] The difference between Comparative Example 5 and Example 1 is the lack of fluorinated paraffin, and the rest of the contents are the same as Example 1.
[0090] Comparative Example 6
[0091] The difference between Comparative Example 6 and Example 1 is that the amount of modified nano-attapulgite exceeds the specified range, specifically 20 g, and the rest is the same as Example 1.
[0092] The coatings prepared in the embodiments and comparative examples were sprayed on the sample steel plates, and the thickness of the sprayed paint film was 80um. After drying, the edges of the steel plates were sealed and the coating performance was tested. The wear resistance test was referred to GB / T 1768-2006. The smaller the wear amount, the better the wear resistance of the coating. The antifouling test was referred to GB / T 5370-2007, the pull-off adhesion test was referred to GB / T5210, and the impact resistance test was referred to GB / T 1732. The artificial accelerated aging test was referred to GB / T 1865, the salt spray resistance test was referred to GB / T 1771, and the heat and humidity resistance test was referred to GB / T 1740-2007. The test indicators were: 38±2℃ temperature and 90±2% humidity. The measured technical indicators are shown in Tables 1 and 2.
[0093]
[0094] As shown in Table 1, compared with the comparative example, the coating prepared in the embodiment of the present invention has better antifouling property, higher wear resistance, adhesion and impact resistance.
[0095] From Examples 1 and 2, it can be seen that adding cerium citrate can increase the wear resistance, antifouling and adhesion of the coating. This is because the cerium ions in cerium citrate interact with certain functional groups in the resin and other organic materials through chelation, which improves the adhesion and toughness of the coating. Secondly, cerium citrate locks the position of fluorinated paraffin in the coating by increasing viscosity or cross-linking, which helps to enhance and persist the hydrophobicity and antifouling properties of the coating.
[0096] It can be seen from Example 1 that the modified nano-attapulgite can undergo cross-linking reactions with other network structures to form a denser cross-linked network, which improves the adhesion, mechanical strength and wear resistance of the coating. Secondly, the modified nano-attapulgite has better dispersibility and can be used as a physical barrier to improve the anti-fouling effect. It can be seen from Examples 2 and 3 that the lack of 2-imidazole-1-ylethylamine or 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane reduces the modification effect, resulting in reduced performance of the coating. It can be seen from Example 4 that the nano-attapulgite after activation treatment adds more sites, further improving the overall performance of the coating.
[0097] Comparative Example 5 shows that the comprehensive performance of the coating is reduced when fluorinated paraffin is lacking. This is because when fluorinated paraffin is lacking, the hydrophobicity and oleophobicity of the coating surface are significantly reduced, and pollutants are more likely to adhere to the coating surface, resulting in reduced antifouling performance. The uniform distribution of fluorinated paraffin can enhance the flexibility and impact resistance of the coating, and at the same time, synergize with modified nano-attapulgite to form a more compact cross-linked network structure. When fluorinated paraffin is lacking, the cross-linked network structure of the coating is not dense enough, and the mechanical properties are reduced, resulting in the coating being more prone to rupture or peeling when impacted by external forces, and the impact resistance and wear resistance are reduced.
[0098] Comparative Example 6 shows that increasing the amount of modified nano-attapulgite reduces the performance of the coating. This is because: high dosage will cause particle accumulation on the coating surface, increase surface roughness, and weaken its antifouling performance (pollutants are more likely to adhere to rough surfaces). Excessive addition of modified attapulgite may destroy the mechanical continuity inside the coating, causing uneven stress distribution, thereby reducing the impact resistance of the coating. However, as the amount of modified nano-attapulgite increases, the agglomeration between particles easily leads to the shedding of wear particles, destroying the coating structure and accelerating wear.
[0099]
[0100] It can be seen from Table 2 that compared with the comparative example, the salt spray resistance, moisture and heat resistance and aging resistance of the coating prepared in the embodiment are improved, indicating that the modified nano-attapulgite significantly improves its dispersibility in the coating matrix by introducing the organic functional groups of 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and the organic functional groups on the surface of the modified nano-attapulgite can undergo chemical cross-linking reaction with the resin matrix in the coating, thereby enhancing the compatibility of the nano-attapulgite with the resin matrix, and forming a more uniform and dense cross-linked network structure in the coating, which can effectively prevent corrosive media (such as Cl⁻ in salt spray, water molecules and oxygen in a humid and hot environment, etc.) from penetrating into the interior of the coating, reducing the defects in the coating (such as micropores, cracks, etc.), thereby improving the coating's anti-permeability, salt spray resistance and moisture and heat resistance. The presence of modified nano-attapulgite can also capture free radicals and inhibit the chain reaction caused by free radicals during the aging process of the coating, thereby delaying the oxidative degradation process of the coating and enhancing the aging resistance of the coating. Modified nano-attapulgite can enhance the density and mechanical properties of the coating, while fluorinated paraffin reduces the surface energy of the coating and reduces the adhesion of moisture and corrosive media. The combination of the two significantly improves the salt spray resistance, moisture and heat resistance and aging resistance of the coating. Therefore, in the absence of fluorinated paraffin, the salt spray resistance, moisture and heat resistance and aging resistance of the coating are all reduced (see Comparative Example 5).
[0101] Modified nano-attapulgite is an inorganic filler whose reinforcing effect depends on the synergistic effect with the resin matrix. When used in moderate amounts, modified nano-attapulgite can improve the mechanical properties of the coating (such as wear resistance, impact resistance, etc.) through chemical crosslinking and physical reinforcement. When used in excessive amounts, the inorganic properties of the modified nano-attapulgite will cause the flexibility of the coating to decrease, and the coating will become fragile and prone to cracking or peeling under external forces. This decrease in mechanical properties will accelerate the degradation of the coating in hot and humid, salt spray and aging environments, and reduce its durability (see Comparative Example 6).
[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An antifouling coating, characterized in that: The antifouling coating comprises component A and component B. Calculated by weight, the component A comprises: 50-70 parts of fluorosilicone modified acrylic resin, 5-8 parts of fluorinated paraffin, 10-15 parts of modified nano-attapulgite, 1-3 parts of wetting agent, 1-3 parts of defoaming agent, and 3-5 parts of dispersant; the component B comprises: 4-6 parts of curing agent and 1-3 parts of diluent; the weight ratio of component A to component B is 8-10:1; The modified nano-attapulgite modifier is prepared from 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; The preparation method of the modified nano attapulgite is: In a nitrogen atmosphere, 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are reacted at 140-160° C. for 4-5 hours under the catalysis of boron trifluoride ether to prepare a modifier; After the nano-attapulgite is treated with arc plasma, it is ultrasonicated in an isopropanol aqueous solution for 20-30 minutes to obtain a suspension, and then a modifier is added, and the ultrasonication is continued for 20-30 minutes. Subsequently, it is refluxed in a nitrogen atmosphere for 3-4 hours and filtered to obtain the modified nano-attapulgite.
2. An antifouling coating according to claim 1, characterized in that: The component A further comprises 1-2 parts by weight of cerium citrate.
3. An antifouling coating according to claim 1, characterized in that: The molar ratio of the 2-imidazole-1-ylethylamine:2-(3,4-epoxycyclohexyl)ethyltriethoxysilane is 1:1-3, and the amount of the boron trifluoride ether is 1%-3% of the total weight of the 2-imidazole-1-ylethylamine and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
4. An antifouling coating according to claim 1, characterized in that: The mass ratio of the nano-attapulgite to the modifier is 1:1-2.
5. An antifouling coating according to claim 1, characterized in that: The wetting agent is fatty alcohol polyoxyethylene ether; the defoaming agent is a polyether defoaming agent; the dispersing agent is a mixture of one or more of 1-hydroxyethyl-3-methylimidazole tetrafluoroborate, 1-hydroxyethyl-3-methylimidazole acetate, 1-hydroxypropyl-3-methylimidazole acetate and 1-hydroxypropyl-3-methylimidazole tetrafluoroborate; the curing agent is an isocyanate curing agent, and the diluent is one of trimethylolpropane glycidyl ether, ethylene glycol glycidyl ether and tert-butyl carbonate glycidyl ether.
6. A method for preparing an antifouling coating according to any one of claims 2 to 5, characterized in that: The following steps are involved: S1, mixing the formulated amounts of fluorosilicone modified acrylic resin, fluorinated paraffin, modified nano-attapulgite, cerium citrate, a wetting agent, a defoaming agent and a dispersant, and stirring to obtain component A; S2, mixing the curing agent and the diluent in the formula amount, stirring, to obtain component B; S3, mix the A component and the B component in the formula amount, stir, and obtain.
7. The method for preparing an antifouling coating according to claim 6, characterized in that: In steps S1-S3, the stirring speed is 800-1500 rpm and the time is 10-30 min.
8. Use of the antifouling coating as claimed in claim 1 in ships and nets and cages.
Citation Information
Patent Citations
Water-based antifouling coating and application thereof
CN112574629A
Process for coating metallic surfaces with an anti-corrosive coating
CN101035630A
Low-emission flame-retardant polystyrene material and preparation method thereof
CN106674856A